Consumer demand for the mobile Internet in a greenfield emerging market: The case of Myanmar - Thaw Tar Min; Elizabeth Fife; Erik Bohlin (International Telecommunications Society (ITS), 2014)
This paper offers a baseline for understanding the mobile Internet market in Myanmar before widespread adoption occurs. The purpose of the paper is to explore consumers' initial demand for existing and future mobile services; the behaviour of mobile users and mobile Internet usage in such a greenfield market where mobile phone services are still emerging. The results of this study are aimed to gain insight into the current dynamics that may become more important when mobile networks and services are in place in near future. The results show that communications is the primary motive for both mobile phone users and non-users. Unexpectedly, gaining help in an urgent situation is the most vital motivation for mobile owners in Myanmar. It is surprising to see that social networking services were highly ranked compared to other mobile services available today. Respondents predict that the future services they will be most willing to use include access to community information and healthcare services. Interestingly, the mobile Internet is the most frequently used Internet services in Myanmar. In addition, demographic factors have a significant effect on mobile Internet usage. Lastly, the study contributes some thoughts for future research.
Keywords: 330; mobile services; consumer demand; Myanmar